Interpretasi Ulama Dayah Terhadap Narasi Moderasi Beragama: Negotiable - Iskandar Zulkarnaen; Muntasir Muntasir; Fauzi Fauzi; Bimby Hidayat (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
The rise of exclusive-formalistic religious interpretations is a series of facts that emphasize how the graph of the seeds of religious radicalism in Indonesia and Aceh, in particular, is increasingly undeniable. Referring to this phenomenon, this research aims to study the strengthening of political democracy and national identity based on local values and culture, which is the standard of political behavior in Aceh. This research method uses descriptive qualitative data from interviews, FGDs, questionnaires, and literature studies. The results obtained: First, the interpretation of Dayah Ulama towards the narrative of religious moderation looks dynamic and varied. On the one hand, in quantity, most Dayah Ulama do not question the narrative of religious moderation, including accepting its derivative concepts. On the other hand, it indicates a form of fragmentation in accepting the narrative of religious moderation. Second, the majority of Dayah Ulama show acceptance of the narrative of religious moderation with pre-conditions. The attitude shown must be based on existing Islamic Sharia and Acehnese customs regulations. Third, conservative and exclusive attitudes appear negotiable, meaning that these attitudes can fade if religious interests are not disturbed.